Effects of antibiotics (enrofloxacin) on microbial community of water and sediment in an aquatic ecological model - Dai, Yue; Peng, Jin-Ju; Zhang, Teng-Yue; Xie, Xing-Peng; Luo, Shuai-Shuai; Liu, Wen-Chao; Ma, Yi (Frontiers in Veterinary Science, 2023)
In order to explore the impact of antibiotics (enrofloxacin) on the microbial community structure in the aquatic environment, an indoor aquatic ecological model was built, and different concentrations of enrofloxacin (0.05, 0.5, 5, 50 mg/L) were added in the aquatic ecological model. In addition, the water and sediment samples were collected on the 0, 7, 30, and 60 days, and the changes in microbial community structure, diversity and abundance were studied through 16S rDNA high-throughput sequencing. The results showed that the average number of operational taxonomic units (OTUs) in sediment samples was 880, and the average number of OTUs in water samples was 311. The diversity and richness of microbial community in sediment were higher than those in water. The maximum and minimum values of Shannon diversity index in sediment and water samples differ by 1.284 and 2.108 respectively. The impact of enrofloxacin on the microbial community structure in water is higher than that in sediment. When the concentration of enrofloxacin was 50 mg/L, the relative abundance of Actinomycetes increased. In the water, the bacterial richness and diversity communities first decreased and then gradually recovered with the passage of time; On the 7th day, the diversity index and richness index of species in the treatment groups with enrofloxacin at 5 mg/L and 50 mg/L decreased to the lowest; On the 30th day, the diversity index and richness index of species began to rise; On the 60th day, the diversity index and richness index of water species began to increase, while the diversity index and richness index of sediment species decreased. When the concentration of enrofloxacin in aquatic ecosystem was 50 mg/L, the abundance of Actinomycetes was increased. In conclusion, the addition of enrofloxacin negatively affected the the microbial community structure in an indoor aquatic ecological model. The results of this study provide theoretical basis for the use of enrofloxacin in aquaculture, as well as for the ecological risk assessment and safety management of enrofloxacin.